Management of Teacher Professional Development at Madrasah Aliyah Negeri (State Islamic Senior High School) - Hatiah Hatiah; M. Syahran Jailani; Madyan Madyan (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
ENGLISH: Management of Teacher Professional Development at Madrasah Aliyah Negeri (State Islamic Senior High School)Objective: This study aims to identify and analyse the management of teacher professionalism development at Madrasah Aliyah Negeri 2 Batang Hari. Method: The research method used is a descriptive qualitative study with data collection techniques through observation, interviews, and documentation. The research subjects include the school principal, teachers, and administrative staff. Data analysis was conducted through data validity checks via extended participation, extended observation, and triangulation. Results: The management of teacher professionalism development at Madrasah Aliyah Negeri 2 Batang Hari is implemented through planning, organising, actuating, and controlling. Teacher professionalism has developed well through the effective leadership of the principal and cooperation between the principal, vice principal, and teachers. Conclusion: Teacher professionalism development at Madrasah Aliyah Negeri 2 Batang Hari has been running well, although several obstacles need to be overcome. The leadership of the madrasah principal plays an important role in encouraging the improvement of teaching quality and teacher professionalism. Contribution: This study contributes to understanding the importance of teacher professionalism development management in madrasahs and the factors that influence its effectiveness.INDONESIAN: Manajemen Pengembangan Profesionalisme Guru di Madrasah Aliyah NegeriTujuan: Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis manajemen pengembangan profesionalisme guru di Madrasah Aliyah Negeri 2 Batang Hari. Metode: Metode penelitian yang digunakan adalah studi kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Subjek penelitian meliputi Kepala Madrasah, guru, dan staf tata usaha. Analisis data dilakukan melalui pengecekan keabsahan data melalui perpanjangan keikutsertaan, perpanjangan pengamatan, dan triangulasi. Hasil: Manajemen pengembangan profesionalisme guru di Madrasah Aliyah Negeri 2 Batang Hari diterapkan melalui tahapan planning, organizing, actuating, dan controlling. Profesionalisme guru telah berkembang dengan baik melalui kepemimpinan kepala madrasah yang efektif, kerja sama antara kepala madrasah, wakil kepala madrasah, dan guru. Kesimpulan: Pengembangan profesionalisme guru di Madrasah Aliyah Negeri 2 Batang Hari telah berjalan dengan baik, meskipun terdapat beberapa faktor penghambat yang perlu diatasi. Kepemimpinan kepala madrasah berperan penting dalam mendorong peningkatan kualitas pengajaran dan profesionalisme guru. Kontribusi: Penelitian ini memberikan kontribusi dalam memahami pentingnya manajemen pengembangan profesionalisme guru di madrasah, serta faktor-faktor yang mempengaruhi efektivitasnya.